Multicultural Learning Design in Education: A Systematic Literature Review of Pedagogical Practice and Innovation - Viky Nur Vambudi; Musa Asy'arie; Sekar Ayu Aryani; Mohamad Ali; Muhammad Badat Alauddin (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
The diversity of cultures, languages, religions, ethnicities, and social identities of students demands a learning design that not only incorporates cultural content, but also transforms strategies, assessments, media, and pedagogical relationships in an inclusive manner. This research aims to analyze the concept of multicultural learning design, identify practices that have been applied in various educational contexts, and map pedagogical innovations that emerge from its application. The research uses the Systematic Literature Review approach with the Scopus database. Articles were selected through the PRISMA flow based on the criteria of empirical, open access, English-language research articles, published in reputable journals in the period 2025-2026, and relevant to the theme of multicultural learning design, so that 30 articles were obtained for thematic analysis. The results show that multicultural learning design develops into a holistic framework that integrates cognitive, affective, social, linguistic, digital, and ideological dimensions. Dominant practices include culturally responsive teaching, translanguaging, culturally responsive assessment, religious moderation, integration of local wisdom, community-based learning, and psychosocial support. Pedagogical innovations include the use of generative AI, cross-cultural simulation, adaptive gamification, interactive digital media, autoethnography, and international collaboration. This study concludes that multicultural learning design needs to be designed as an equitable, reflective, adaptive, and transformative learning ecosystem.